2016
DOI: 10.1017/s0029665116000628
|View full text |Cite
|
Sign up to set email alerts
|

Circadian rhythms, food timing and obesity

Abstract: It is known that our physiology changes throughout the day and that several physiological hormones display circadian rhythmicity. The alteration of this normal pattern is called chronodisruption (CD). In recent years, it has been demonstrated that CD is related to obesity. Although several factors may be causing CD, one important aspect to consider is the failure in our internal clock. Indeed, studies performed in mutant animals have demonstrated that mutations in clock genes are related to obesity. In human s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(37 citation statements)
references
References 39 publications
1
35
0
1
Order By: Relevance
“…Studies of workers and the general population have shown that changes in the pattern of meals are an independent risk factor for weight gain (56), glucose intolerance, insulin resistance, dyslipidemia and obesity (57)(58)(59). Skipping breakfast is associated with excess weight and changes in metabolic markers, regardless of total caloric intake (60)(61)(62). In addition, the increased consumption of food and calories during the night has also been associated with metabolic changes and weight gain (62)(63)(64)(65).…”
Section: Discussionmentioning
confidence: 99%
“…Studies of workers and the general population have shown that changes in the pattern of meals are an independent risk factor for weight gain (56), glucose intolerance, insulin resistance, dyslipidemia and obesity (57)(58)(59). Skipping breakfast is associated with excess weight and changes in metabolic markers, regardless of total caloric intake (60)(61)(62). In addition, the increased consumption of food and calories during the night has also been associated with metabolic changes and weight gain (62)(63)(64)(65).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we have analysed PER3 methylation, and we have confirmed the negative correlation between this gene and childhood obesity that was observed in the microarray. Interestingly, several studies described the role of the methylation of a related gene ( PER2 ) in obesity and metabolic syndrome .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we have analysed PER3 methylation, and we have confirmed the negative correlation between this gene and childhood obesity that was observed in the microarray. Interestingly, several studies described the role of the methylation of a related gene (PER2) in obesity and metabolic syndrome (22,24). The negative association between BMI z-score and methylation levels of PTPRS and PER3 indicates that children with high methylation levels presented lower degree of obesity.…”
Section: Discussionmentioning
confidence: 99%
“…CCGs adjust the internal environment so that the organism can function optimally. Hierarchically, there are mechanisms that synchronize CCGs with the outer environment (for example timing of food intake) [20][21][22].…”
Section: Introductionmentioning
confidence: 99%